IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE MAKE A MATCH TO IMPROVE CONCEPTS COMPREHENSION OF TWO DIMENTIONAL FIGURE CHARACTER - Santri Prabowo Utomo; Sukarno Sukarno; Muhammad Ismail Sriyanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research is to improve concepts comprehension two dimentional figure character through the implementation of cooperative learning model type Make a Match. The source of the data comes from teachers, students, and researches. The data collection technique is by test, interview, observation, and documentation. The validity of the data used content validity and data triangulation. The data analysis used interactive data analysis by Miles and Huberman (2014) which consist of data reduction, data presentation, and conclusion. The results of this research is the average scores that students classical mastery cycle I and cycle II increased. The average scores is 87,5 in cycle II with students classical mastery 88,89% or 16 students of 18 students is completed. The conclusion of this research is through the implementation of cooperative learning model type Make a Match can improve concepts comprehension mathematics leaning about two dimentional figure character.